2018
DOI: 10.20524/aog.2018.0255
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C coinfection in a real-life setting: viral interactions and treatment issues

Abstract: Background:Only limited data concerning hepatitis B (HBV) and C viruses (HCV) coinfection are available. Direct-acting antivirals (DAAs) may be more effective for HCV clearance than interferon (IFN)-based regimens with a risk of HBV reactivation.Methods:We retrospectively enrolled 40 HBV/HCV-coinfected patients to evaluate their clinical profile and treatment outcomes.Results:Chronic dual infection was present in 25/40 (62.5%) patients, acute HCV superinfection in 5/40 (12.5%) patients and acute HBV superinfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…A mutual influence between HBV and HCV replication has already been found. [8][9][10][45][46][47] Higher HCV activity in HBV-coinfected patients with a related HCV suppressing effect on HBV replication has also been demonstrated. 9,45,[48][49][50] In addition, the successful elimination of HCV resulted in some cases in an HBV 12,49,51 Although the restricted availability of samples/patients greatly limited a deeper investigation into HBV, to date, this is the first study that has shown a potential impact of HBV co-infection also on HCV variability and/or compartmentalization.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A mutual influence between HBV and HCV replication has already been found. [8][9][10][45][46][47] Higher HCV activity in HBV-coinfected patients with a related HCV suppressing effect on HBV replication has also been demonstrated. 9,45,[48][49][50] In addition, the successful elimination of HCV resulted in some cases in an HBV 12,49,51 Although the restricted availability of samples/patients greatly limited a deeper investigation into HBV, to date, this is the first study that has shown a potential impact of HBV co-infection also on HCV variability and/or compartmentalization.…”
Section: Discussionmentioning
confidence: 93%
“…To date, HBV-HCV chronic coinfection is estimated to be between 0.7% and 17.8%, depending on geographical regions and study populations. 8,9 The interplay between the two infections has a high association with more aggressive cirrhosis and the establishment of HCC. [9][10][11] Moreover, HBV reactivation in patients treated for HCV with directacting agents (DAAs) has recently emerged as an important clinical consideration.…”
Section: Introductionmentioning
confidence: 99%
“…16 Hepatitis B virus (HBV) and hepatitis C virus (HCV) have several important similarities including worldwide distribution, hepatotropism, similar modes of transmission and the ability to induce chronic infection that may lead to liver cirrhosis and hepatocellular carcinoma. 17 Acute HBV/HCV co-infection is more prevalent in patients who inject drugs. 18 Co-infected patients represent a diverse group with various patterns of viral replication and great variations of immune profile.…”
Section: Introductionmentioning
confidence: 99%
“…Type I Interferons (IFN-I) are cytokines composed mainly by IFN-α and β [ 1 ], which have important roles in innate and adaptive immune responses with effects over a broad range of mammalian cells [ 2 , 3 ]. The type I IFN display broad biological activity, including control of cell proliferation, induction of genes responsible for protecting cells against the effects of viral infection, regulation of the differentiation state of immune cells and modulation of their function, accordingly these cytokines have been used in the treatment of viral and proliferative disease [ [4] , [5] , [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%